Diacerein in the treatment of osteoarthritis in patients with comorbidity - E. P. Sharapova; L. I. Alekseeva; A. M. Lila (Современная ревматология)
Osteoarthritis (OA) belongs to diseases with high comorbidity and is most frequently concurrent with hypertension and other cardiovascular diseases (coronary heart disease, atherosclerosis), obesity, and diabetes mellitus. The paper deals with the use of delayed-release symptomatic medications in the treatment of patients with OA and comorbidity. It reviews clinical trials of the efficacy and safety of diacerein in OA patients and its effect on comorbidity. The paper discusses the possibility of using diacerein as an alternative to traditional nonsteroidal anti-inflammatory drugs in patients with contraindications to the latter.